Oracle BPM Suite 11g : advanced BPMN topics : master advanced BPMN for Oracle BPM Suite including inter-process communication, handling arrays, and exception management /: advanced BPMN topics : master advanced BPMN for Oracle BPM Suite including inter-process communication, handling arrays, and exception management. (2012) - Unknown
No abstract available